1990
DOI: 10.1159/000235306
|View full text |Cite
|
Sign up to set email alerts
|

Generation and Metabolism of Leukotrienes in Granulocytes of Patients with Cystic Fibrosis

Abstract: We studied the generation and metabolism of lipoxygenase products in peripheral granulocytes from children suffering from cystic fibrosis (CF). Peripheral granulocytes were stimulated at different times (days) before and during anti-infectious treatment with the Ca ionophore (7.5 μM, 5 and 20 min), opsonized zymosan (2 mg) and arachidonic acid (50 μM); the amount of lipoxygenase products in the cell supernatants was determined by high performance liquid chromatography. Granulocytes from patients with CF, compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0
1

Year Published

1992
1992
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 14 publications
2
8
0
1
Order By: Relevance
“…In contrast, some clinical trials involving LTB 4 modulators reported pulmonary infections as severe adverse events indicating that in humans, LTB 4 should not be regarded as a pro‐inflammatory effector but rather as a booster of innate immunity and host defense. Of note, the ω‐LTB 4 /LTB 4 ratio is increased in neutrophils purified from the blood of cystic fibrosis patients and from severely burned patients, two conditions in which infections are not well controlled. Furthermore, 20‐OH‐LTB 4 and 20‐COOH‐LTB 4 were detected in the sputum of patients with cystic fibrosis in larger amount than LTB 4 itself (55% 20‐COOH‐LTB 4 :20% 20‐OH‐LTB 4 :25% LTB 4 ) .…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, some clinical trials involving LTB 4 modulators reported pulmonary infections as severe adverse events indicating that in humans, LTB 4 should not be regarded as a pro‐inflammatory effector but rather as a booster of innate immunity and host defense. Of note, the ω‐LTB 4 /LTB 4 ratio is increased in neutrophils purified from the blood of cystic fibrosis patients and from severely burned patients, two conditions in which infections are not well controlled. Furthermore, 20‐OH‐LTB 4 and 20‐COOH‐LTB 4 were detected in the sputum of patients with cystic fibrosis in larger amount than LTB 4 itself (55% 20‐COOH‐LTB 4 :20% 20‐OH‐LTB 4 :25% LTB 4 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, chemotaxis in CF might be impaired due to differential responsiveness to stimulants or chemoattractants. Previous studies have suggested that the lipoxygenase pathway and resulting leukotrienes are involved in CF lung disease (Saak et al, 1990). Leukotriene B4 (LTB 4 ) has been further associated with impaired neutrophil chemotaxis in patients with rheumatoid arthritis, chronic bowel disease and CF (Lawrence and Sorrelli, 1992).…”
Section: Circulating Neutrophilsmentioning
confidence: 99%
“…For example, neutrophils and eosinophils isolated from CF patients have been shown to have an altered arachidonic acid turnover [12], and an increased release of myeloperoxidase (MPO), eosinophil cationic protein (ECP), and eosinophil protein X (EPX) [13]. In addition, isolated peripheral neutrophils from CF patients generated higher levels of elastase when exposed to stimuli such as IL-8 and TNFa compared to neutrophils isolated from controls [14].…”
Section: Introductionmentioning
confidence: 99%